Relative Pricing of Eurodollar Futures and Forward Contracts - GRINBLATT, MARK; JEGADEESH, NARASIMHAN (Journal of Finance, 1996)
ABSTRACT Past research explains observed spreads between futures and forward Eurodollar yields as being due to the futures contract's mark‐to‐market feature. We derive closed form solutions for this yield spread and show that, theoretically, it should be small. Also, differences in liquidity, taxation, and default risk cannot account for the large spreads observed. We also present evidence that the spreads, which are nonnegligible primarily in the first half of the sample period, are likely to be attributable to the mispricing of futures contracts relative to the forward rates and that the mispricing was gradually eliminated over time.